Syphilis screening during prenatal development: missed opportunities in a public maternity hospital in Recife, Brazil - Freire Júnior, Manoel Bastos; Freire, Georges Kelbert de Albuquerque; Fernandes, Humberto Rochimin (Brazilian Journal of Sexually Transmitted Diseases, 2016)
Introduction: According to the norms issued by the Ministry of Health for the Prenatal and Birth Humanization Program, pregnant women should undergo two tests for syphilis detection. Objective: To evaluate missed opportunities for screening gestational syphilis and to identify factors associated with the missing application of the Venereal Disease Research Laboratory (VDRL) test during prenatal development. Methods: This cross-sectional study was undertaken in the maternity ward of a Unified Public Health System (SUS) hospital in the city of Recife in northeastern Brazil. We studied 460 women admitted for termination of pregnancy and/or abortion, between September and October 2013, who had at least one prenatal consultation. We conducted interviews and checked patients’ prenatal care records and medical records. Women who did not take at least one VDRL test during prenatal development (reference category) were compared with those who did. Logistic regression was performed on the data collected from the 408 pregnancy records analyzed in order to identify factors associated with a failure to undergo syphilis screening. Results: 17.90% of the women in the sample did not take the VDRL test. In multivariate analysis, women who fit the following factors presented a greater chance of not having taken the VDRL test: facing difficulties in taking the test; attendance of the last prenatal consultation before the last trimester of pregnancy; attending less than six consultations; receiving prenatal care in hospital units which did not schedule subsequent exams; being 19 years of age or younger; having had three or more pregnancies. Conclusion: Results show that despite the high availability of prenatal care, actions aimed at preventing congenital syphilis still present low effectiveness.